Referral conditions for severe road traffic injuries and their influence on the occurrence of hospital deaths in Benin - Bella Hounkpe Dos Santos; Yolaine Glele Ahanhanzo; Alphonse Kpozehouen; Donatien Daddah; Edgard-Marius Ouendo; Yves Coppieters; Alain Leveque (AOSIS, 2022)
Road traffic accidents are the leading cause of death by trauma. Delays in in first aid due, inter alia, to the long time to transfer traffic accident victims to hospital and the lack of pre-hospital emergency care, contribute to the increase in hospital mortality. This study aims to analyse the referral conditions for severe road traffic injuries and to assess their effect on the occurrence of hospital deaths in Benin. This is an analytical prospective cohort study conducted in road accident victims with a severe injury. Four groups of factors were studied: referral conditions, sociodemographic and victim-specific characteristics, factors related to the accident environment, and factors related to health services. A top-down binary stepwise logistic regression was the basis for the analyses. Nine point eight percent of severe trauma patients died after hospital admission (7.0-13.5). Associated factors were referral time greater than 1 hour (RR=5.7 [1.5-20.9]), transport to hospital by ambulance (RR=4.8 [1.3-17.3]) and by the police or fire department (RR=7.4 [1.8- 29.7]), not wearing protective equipment (RR=4.5 [1.4-15.0]), head injuries (RR=34.8 [8.7-139.6]), and no upper extremity injuries (RR=20.1 [2.3-177.1]). To reduce the risk of hospital death in severe road traffic injuries, it is important to ensure rapid and medicalized referral of severe trauma patients in Benin.